Design of ceramic filters using Clay/Sawdust composites: Effect of pore network on the hydraulic permeability. Issue 5 (1st April 2017) - Youmoue, Martine; Fongang, R.T. Téné; Sofack, J.C.; Kamseu, Elie; Melo, U. Chinje; Tonle, Ignas K.; Leonelli, C.; Rossignol, Sylvie
Abstract: Clay based ceramic composite materials with hydraulic permeability were elaborated using sawdust as porogent agent. Their mechanical, morphological, microstructural and pore network properties were investigated. Mixtures in various ratios of two kaolinite clay minerals, Ba (highly plastic) and Va (sand-rich) constitute the five ceramic matrixes studied (CM1, CM2, CM3, CM4 and CM5). Due to their high flexural strength, CM3 and CM4 received 0%, 5%, 10% and 15% sawdust before firing, to improve the porosity of the final matrixes. Results revealed that 900–1000 °C is the range of temperature necessary to get good sintering and flexural strength (≥2 MPa). A typical clay-sawdust based materials (parallepipedic bricks) present porosity ≥40 vol% and 1.5 g/cm 3 density. Characterizations such as FTIR, SEM, MIP and flow permeability of ceramic candles were performed. A Hydraulic permeability of 10 mDarcy was obtained and the mean pore diameter varies from 0.05 to 0.1 µm, in agreement with the microstructure exhibited by the ceramic candles. In the presence of sawdust, pores with size up to 10 µm were observed, justifying the increase of flowing permeability. The elaborated matrixes are promising candidates for microfiltration.